Analysis of the problem-based learning (PBL) models on geometry material in improving students' mathematics learning outcomes - Fathul Bhary; Maswar Maswar; Moh. Atikurrahman; Ahmad Afandi (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2023)
This study aimed to describe the increase in students' learning outcomes of geometry material at MTs Nuris Jember used a problem-based learning model. This type of research was classroom action research with a model design consisting of four steps: planning, acting, observing, and reflecting. Data collection techniques used tests and observations. The instruments used essay questions and checklists of student activities in class. Thirty students of class VII at MTs Nuris Jember served as the subjects, and samples were collected using purposive random sampling. In this study, descriptive and inferential statistics were employed in the data analysis for this investigation. It could be seen from the research results that the initial condition of the average test score was 61.33, meaning that 30% of students had passed the learning in the pre-cycle. In standard Cycle I, the average test score was 66.83, and 47% of students had reached standard learning. In Cycle II, the average score of students' tests was 71.67, and 83% of students had reached the standard learning. The significance test results of the average value showed a significant difference in average test results between students' mathematics learning outcomes in Cycle I and Cycle II, with a significance value of 0.000, which is less than 0.05. Based on the observation result of students' activity in the second Cycle, the average observation result for students' activities was 79,45% in the good category and got an alphabet score of B.